Stability and lifetime study of carbon nanotubes as cold electron field emitters for electron cooling in the CERN extra low energy antiproton ring - Bruno Galante (American Physical Society, 2021)
Electron cooling is a fundamental process to guarantee the beam quality in low energy antimatter facilities. In extra low energy antiproton, the electron cooler reduces the emittance blowup of the antiproton beam and thus delivers a focused and bright beam to the experiments at the unprecedentedly low kinetic energy of 100 keV. In order to achieve a cold beam at this low energy, the electron gun of the cooler must emit a monoenergetic and relatively intense electron beam. An optimization of the extra low energy antiproton electron cooler gun involving a cold cathode is studied, with the aim of investigating the feasibility of using carbon nanotubes (CNTs) as cold electron field emitters. CNTs are considered among the most promising field emitting material. However, stability data for emission operation over hundreds of hours, as well as lifetime and conditioning process studies to ensure optimal performance, are still incomplete or missing, especially if the purpose is to use them in operation in a machine such as extra low energy antiproton. This manuscript reports experiments that characterize these properties and ascertain whether CNTs are reliable enough to be used as cold electron field emitters for many hundreds of hours.